The Importance of Health Literacy During COVID-19 Pandemic (Turkey Health Literacy Journal, 2021)
On 31 December 2019, the World Health Organization China Country Office was informed of cases of pneumonia unknown etiology (unknown cause) detected in Wuhan, China and on 7 January 2020, the agent was identified as a new coronavirus (2019-nCoV) that was not previously detected in humans. The WHO classified the COVID-19 outbreak as an "international public health emergency" on 30 January 2020, with the occurrence of COVID-19 cases in 113 countries except China, where the first outbreak started, was defined as a global epidemic (pandemic) on March 11 due to the spread and severity of the virus. The rapid transformation of COVID-19 disease into a pandemic has forced people to learn about this virus, practice it, and make a rapid change of behavior in their lives. During this process, information about COVID-19 began to be shared on various platforms and apprehension and anxiety have increased in society, which has not encountered most measures such as medical terms, use of masks and social distance contained in shared information, and the spread of misinformation on social platforms has accelerated. During this period, the importance of health literacy has increased and many studies were conducted. In this study, current literature on the subject was examined and it was aimed to draw attention to the importance of the health literacy.